2012
DOI: 10.3349/ymj.2012.53.6.1216
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-Assisted Microsurgical Removal of an Epidermoid Tumor within the Cavernous Sinus

Abstract: Epidermoid tumor of the cavernous sinus is rare. The aim of this case report is to discuss the role of neuroendoscopes in the removal of such lesions. A 21-year-old man presented with 6-year history of progressive headache, diplopia, and visual disturbance. Work-up revealed an epidermoid tumor located in the right cavernous sinus. An extradural transcavernous approach was utilized via a traditional frontotemporal craniotomy with endoscopic assistance. The postoperative course was uneventful with immediate impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Review of the literature (Table 5) revealed 7 publications, 10,27,29,33,45,56,68 4 of which focus on endoscopic CS biopsy. 27,29,45,68 One is a case report of endoscope-assisted microsurgery on a CS epidermoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of the literature (Table 5) revealed 7 publications, 10,27,29,33,45,56,68 4 of which focus on endoscopic CS biopsy. 27,29,45,68 One is a case report of endoscope-assisted microsurgery on a CS epidermoid.…”
Section: Discussionmentioning
confidence: 99%
“…27,29,45,68 One is a case report of endoscope-assisted microsurgery on a CS epidermoid. 10 The other 2 are mixed series that also include pituitary adenomas and meningiomas. 33,56 Hence, the current report is the largest systematic study on the results of endoscopic endonasal surgery of lesions other than adenomas and meningiomas within the CS to our knowledge to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracranial epidermoid cysts are an uncommon finding, 5,21,31 and epidermoid cysts of the CS are even rarer, accounting for only 2% of all intracranial epidermoid tumors. 31 At our center, lesions of the CS account for 4.3% of all epidermoid cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopes also help to minimise the retraction of neuro vascular structures. Fries and Perneczky described the advantages of the endoscopes as an adjunct tool in micro surgery including reduced surgical trauma, especially in a vascular lesions such as epidermoid tumor [5]. Expanded endonasal transsphenoidal approach has advantages of no incisions, faster recovery, early devascularisation of tumour, no brain retraction, minimal manipulation of optic apparatus, avoids craniotomy, less post operative discomfort and no loss of olfaction.…”
Section: Discussionmentioning
confidence: 99%